Local Government Planning in the Development of School Education Quality - Ramadani, Nursiva; Riskiati, Nadya; Yanti, Sharah Ramadha; Erinaldi, Erinaldi (Civiliza Publishing, Indonesia., 2025)
This study aims to uncover the role of educational planning in improving education quality, emphasizing the importance of a focused and sustainable strategy at the educational unit level. This study employed a literature review method, reviewing various sources, including previous research, educational policy documents, and school performance reports. Through descriptive analysis, this study sought to understand the extent to which educational planning effectively supports educational quality improvement. The study's findings indicate that educational planning, in general, is not fully oriented toward comprehensive educational goals. However, improvements in educational quality have begun to be evident through various efforts by school principals to improve the learning process and school management. The main obstacles to educational planning include a lack of administrative staff skilled in strategic planning and limited supporting resources. This study also found that quality improvement measures have been implemented, including recruiting teachers with appropriate competencies, providing training to enhance learning quality, and periodically procuring facilities and infrastructure. In conclusion, educational planning plays a crucial role in promoting educational quality improvement, but it requires strengthening the capacity of planners and more comprehensive policy support for optimal and sustainable implementation.